Traumatic stress symptoms and PTSD risk in children served by Children’s Advocacy Centers - McGuier, Elizabeth A.; Campbell, Kristine A.; Byrne, Kara A.; Shepard, Lindsay D.; Keeshin, Brooks R. (Frontiers in Psychiatry, 2023)
Purpose Children who experience maltreatment are at high risk for posttraumatic stress disorder (PTSD). Children’s Advocacy Centers (CACs) can facilitate access to treatment following maltreatment allegations. We describe PTSD symptoms and intervention decision-making for children served by CACs. Methods Children served by CACs in a single state were screened for PTSD symptoms using a structured mental health screening/referral protocol. CAC staff used an electronic form that provided guidance for decision-making. We examined descriptive statistics for PTSD symptoms and risk and tested associations between child characteristics and symptoms. We described CAC staff’s delivery of brief interventions and referral decisions and tested associations with child characteristics and symptoms. Results Two thousand and three hundred fifty children completed screening between 2018 and 2020. Almost half (45.5%) exhibited traumatic stress symptoms suggesting high probability of PTSD at the time of their CAC visit. Children who identified as female or transgender male and older children were more likely to be at high risk for PTSD. Brief interventions were delivered to 66% of children, and most were referred to evidence-based trauma treatment (53.1%) or community mental health services (39.0%). Categorization as moderate or high PTSD risk was associated with a higher likelihood of brief intervention delivery and referral to trauma treatment. Conclusion Many children served by CACs are likely to meet criteria for PTSD at their initial visit. CAC staff demonstrated the ability to deliver brief interventions and make referrals to mental health treatment. Use of structured screening/referral protocols may improve early identification and treatment access for children experiencing PTSD symptoms.